Theoretical aspects of the predictional instrumentation for application in the state regulation of the participants relationships in the electricity market - Koliesnichenko, Anastasiia (Baltija Publishing, 2017)
The article presents the problems of current trends in the development of the electric power industry in conditions of increasing capital concentration, informing the economy and increasing the dynamics of the movement of significant amounts of cash flows which require a permanent analysis of the current situation and the necessary adjustment and / or modification of the parameters for the regulation of energy markets. From this article it can be concluded that the task of constructing forecasts acquires high relevance in many subject areas. It is an integral component of the daily work of modern social and economical systems. The interrelations of the subjects of the electric energy market are the one of the its most important institutions. The purpose of this article is to study the theoretical basis for the adaptive application of forecasting methods in the functioning of energy markets. In order to avoid the dominance of commercial interests of certain groups of participants in the energy market, the emergence of price distortions in the market that have a destructive effect on obtaining potential benefits from the introduction of competitive mechanisms, the key to finding the most effective and economical way to solve these problems is the use of systemic regulation of emerging deviations in achieving target milestones especially in the context of reform. The informational and analytical support formation for the performance of the functions assigned to the regulatory apparatus requires the use of forecasting methods and approaches to preserve the dynamic development of the electric energy market and to maintain the balance of interests of all its subjects in the conditions of reform. The article uses a number of methods: classification and systematization in the analysis of scientific methods for forecasting and planning social and economic processes, logical generalization when reviewing existing modeling methods and assessing their effectiveness in the energy markets, the use of a constructive approach in the study of factors affecting the resulting index. Finally the obtained theoretical and scientifically applied results of the research make it possible to formulate the necessary theoretical and methodological basis for improving the instrumental basis for modeling the relationships between the subjects of the electric energy market, which can be used in forecasting in the field of regulation of phenomena and processes in the energy markets.

Современные тенденции развития электроэнергетики в условиях нарастания концентрации капитала, информатизации экономики и повышения динамики движения значительных объемов денежных потоков требует перманентного анализа текущей ситуации и необходимой корректировки и/или модификации параметров регулирования энергорынков. Задача построения прогнозов приобретает высокую актуальность во многих предметных областях и выступает неотъемлемой компонентой повседневной работы современных социально-экономических систем, одним из важнейших институтов которых выступают взаимоотношения субъектов рынка электрической энергии. Целью данной статьи выступает исследование теоретической базы касательно адаптивного применения методов прогнозирования в области функционирования энергорынков. Во избежание доминирования коммерческих интересов определенных групп участников энергорынка, появления ценовых перекосов на рынке, которые оказывают деструктивное воздействие на получение потенциальных выгод от внедрения конкурентных механизмов, ключом к поиску максимально эффективного и экономичного пути решения данных проблем выступает применение системного регулирования возникающих отклонений при достижении целевых ориентиров, особенно в условиях реформирования. Формирование информационно-аналитического обеспечения выполнения возложенных функций на аппарат регулирования требует применения прогностических методов и подходов для сохранения динамического развития рынка электрической энергии и соблюдения сбалансированности интересов всех его субъектов в условиях реформирования. В статье использован ряд методов: классификации и систематизации при анализе научных методов прогнозирования и планирования социально-экономических процессов; логического обобщения при обзоре существующих методов моделирования и оценке их эффективности в области энергорынков; обосновано применение конструктивного подхода при исследовании факторов, влияющих на результирующий показатель моделирования. Полученные теоретические и научно-прикладные результаты исследования позволяют сформировать необходимую теоретическую и методическую базу для усовершенствования инструментальной основы моделирования взаимоотношений субъектов рынка электрической энергии, которую можно использовать при прогнозировании в области регулирования явлений и процессов энергорынков.
Теоретические аспекты применения прогностического инструментария в области государственного регулирования взаимоотношений субъектов рынка электроэнергии
Keywords: регулирование; рынок электрической энергии; субъекты энергорынка; методы прогнозирования; regulation; energy market; energy market participants; forecasting methods